Sufi Traditionalism, the Radical Right, and Swedish Islam: The Work and Legacy of Tage Lindbom - Sibgatullina, Gulnaz Rifkhatovna (Journal of religion in Europe, 2025)
The article examines the life and work of Tage Lindbom (1909-2001), a Swedish conservative philosopher, convert to Islam and a prominent figure within the early Swedish Social Democratic Party. His intellectual impact extends beyond shaping post-Second World War conservative thought in Sweden, as we show that his ideas have proven influential for a contemporary cohort of conservative thinkers of diverse backgrounds, including both Muslim and non-Muslim, operating within Sweden’s evolving multicultural landscape. The article highlights the authoritative role occupied by white European converts to Islam among the younger generation of Muslims, and underscores the potential merger of various strands of antiliberal critique produced from majority and religious-minority positions.